Goldsmith Workers (GSWs): A Skilled Job & Status of Illness (Anwer Khan Modern Medical College Journal, 2017)
Background: This study was conducted among the goldsmith workers of different goldsmith's workshops located Islampur of Dhaka city to find out respiratory illness among them. `Methodology: It was a descriptive cross sectional study. By purposive sampling a total of 120 goldsmith workers were interviewed about respiratory problems using questionnaire and checklist.Result: The study revealed out of 120 respondents 5% were illiterate, 40% had education upto Primary level and 55% respondents had education at secondary level and above. Around 31.7% and 30.8% respondents had monthly income 7100-9000 and 9100-11000 taka respectively. Most of them had length of service 6-20 years (72.5%) and 25.8% had length of service >20 years. The study showed 37.5% had been suffering from respiratory illness and among them 75.6% were suffering from cough for 3months or more in a year, 66.7% suffering from cough with phlegm, 18.9% Blood mixed phlegm, 71.1% running nose/ sneezing and 33.3% were suffering from breathlessness. 96.7% respondents had knowledge on use of personal protective equipments (PPE). Around 58.3% respondents were smoker and their mean duration of smoking habit was 15.59 ( 7.36) years. PEFR was significantly low (p